ANALISIS BREAK EVEN POINT SEBAGAI PERENCANAAN LABA USAHA KELOMPOK TANI SARI BUAH DI KELURAHAN LEMBAH SARI KECAMATAN RUMBAI PESISIR - Ritawiyati Ritawiyati; Sri Maryanti; Muhammad Thamrin (Program Studi Pendidikan Ekonomi Universitas Riau, 2019)
The Aneka Rasa Krupuk effort of Sari buah group is a farmer group businesslocated in the Lembah Sari area of Rumbai Peisisir District, which all membersconsist of housewives who make home-based business such as snack making. Saribuah Farmer Group is chaired by Mrs. Sutarti who makes processed sweet potatocrackers and banana crackers, the processed can only be marketed or based onone's order. In the way of farmers group effort conventionally and manually, startingfrom production process until its sale. Every day the farmer group always produce inlarge quantity but, in the planning of sale not yet arranged well and not yet havegood profit plan, this is found at the time of preliminary survey, hence the requiredanalysis of Break Even Point. Break even point analysis is a matter of concern incompany management as it is part of cost analysis. Sales volume, profit. Thepurpose of research to know the break even point as profit planning, while the typeand source of data using secondary data, secondary data can be obtained from therecord of costs, sales, through documents owned by farmer group sari buah. Metoderesearch with the method of calculating break even point in mathematically usingboth units in Rupiah and in Units. Based on data analysis conducted at farmer groupSari buah of Lembah sari sub district of Rumbai Pesisir, hence the conclusion thatdetermining break Eve Point (BEP) for every company, including small industry isone of the planning that need to be done by business owner. to achieve a breakeven point of sale in rupiah production of krupuk group of sari buah farmers must beable to sell the same product with Rp. 19,647,000 in each month or more of the sale.And to reach a unit that can be sold to cracker yam group sari buah farms do notsuffer losses, it must be able to sell 767 kg in each month.